Tingkat Kepuasan Lansia Tentang Pelayanan Kesehatan di Panti Khusnul Khotimah Pekanbaru - Chairil; Ika Wahyuni Utami Rambe (LPPM Universitas Muhammadiyah Riau, 2022)
Elderly is one period in the span of human life that is considered a phase of decline. This is because in this phase an individual experiences various kinds of setbacks in his life such as physical setbacks and cognitive functions which result in the elderly often being seen as troublesome beings. The purpose of this study is to provide the level of satisfaction of the elderly about health services in the Pekanbaru special sermon. The research design used in this study was a quantitative descriptive method, carried out on 16 to 02 February 2019 in the special care home of Pekanbaru. The population in this study amounted to 70 elderly in the Social home care Khusnul Khotimah of Pekanbaru with a sample of 60 respondents using the Purposive Sampling method. Data collection techniques using a questionnaire and data analysis used was univariate. The results of the study prove that with a satisfied category, 32 respondents (53%) with Tangible satisfaction level. The conclusion is that based on the research it is expected that health workers are able to provide health education about health services and provide the level of satisfaction of the elderly in the social home care Khusnul Khotimah Pekanbaru.